RECHERCHES EN TERRAINS « DESIGNES »: EXPERIENCE D’UN SOCIO-ANTHROPOLOGUE INVITE DANS LA NEBULEUSE DE LA LUTTE CONTRE LA TRAITE DES ENFANTS AU BENIN. - IMOROU, ABOU-BAKARI (My University, 2015)
This text aims to trace the trajectory of a solicitation of anthropology in the field of the fight against child trafficking in Benin and constraints of objectification in a very normative space and morally responsible by actors Protection Children that criminalize people accused of engaging their children in trafficking routes. For ten years, the Beninese government and various non-state partners are committed in the fight for better protection of children against the various practices which erode children's development in the Republic of Benin. The child protection discussed here appears as a nebula in which the actors move as diverse as government, international agencies, national NGOs, grassroots. It is also the meeting place of great logical diversity, as one legitimate than others in the eyes of their owners. It is finally the place of an investment "against-productive" for many agencies involved for many years for a better life and greater respect for children's rights. Anthropology is then invited to help understand the logic behind the behavior of various actors involved in the phenomenon and give the strings more suitable actions in a legal-normative universe.
Keywords: involvement; child protection; fight against trafficking; socio-anthropology; Benin